iNOS expressing macrophages co-localize with nitrotyrosine staining after myocardial infarction in humans - Wilmes, Verena; Kur, Ivan M.; Weigert, Andreas; Verhoff, Marcel A.; Gradhand, Elise; Kauferstein, Silke (Frontiers in Cardiovascular Medicine, 2023)
Introduction Inducible nitric oxide synthase (iNOS) produces micromolar amounts of nitric oxide (NO) upon the right stimuli, whose further reactions can lead to oxidative stress. In murine models of myocardial infarction (MI), iNOS is known to be expressed in infiltrating macrophages, which at early onset enter the infarcted zone and are associated with inflammation. In contrast cardiac tissue resident macrophages are thought to enhance regeneration of tissue injury and re-establish homeostasis. Both detrimental and beneficial effects of iNOS have been described, still the role of iNOS in MI is not fully understood. Our aim was to examine cell expression patterns of iNOS and nitrotyrosine (NT) production in human MI. Material and Methods We examined in postmortem human MI hearts the iNOS mRNA expression by means of qPCR. Further we performed immunohistochemical stainings for cell type identification. Afterwards a distance analysis between iNOS and NT was carried out to determine causality between iNOS and NT production. Results iNOS mRNA expression was significantly increased in infarcted regions of human MI hearts and iNOS protein expression was detected in resident macrophages in infarcted human hearts as well as in controls hearts, being higher in resident macrophages in MI hearts compared to control. Furthermore in MI and in healthy human hearts cells showing signs of NT production peaked within 10–15 µm proximity of iNOS+ cells. Discussion These results indicate that, unexpectedly, resident macrophages are the main source of iNOS expression in postmortem human MI hearts. The peak of NT positive cells within 10–15 µm of iNOS+ cells suggest an iNOS dependent level of NT and therefore iNOS dependent oxidative stress. Our results contribute to understanding the role of iNOS in human MI.